Optimal Investment - Rogers, L. C. G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Readers of this book will learn how to solve a wide range of optimal investment problems arising in finance and economics. Starting from the fundamental Merton problem, many variants are presented and solved, often using numerical techniques that the book also covers. The final chapter assesses the relevance of many of the models in common use when applied to data.
Preface -- The Merton Problem -- Variations -- Numerical Solution -- How Well Does It Work -- Index -- References.
Keywords: Mathematics; Finance; Numerical analysis; Mathematical optimization; Mathematics; Quantitative Finance; Finance/Investment/Banking.; Numerical Analysis; Calculus of Variations and Optimal Control; Optimization